Pengaruh Brand Image, Inovasi Produk Dan Kualitas Produk Terhadap Keputusan Pembelian Pada Warung Makan Ayam Nyungsep Kecamatan Dau Kabupaten Malang - Mat Bahri; Nur Hidayati; Pardiman Pardiman (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractPurchasing decisions will affect the sustainability of a business. This study aims to examine the extent of the influence of brand image, product innovation and product quality on purchasing decisions at Nyunsep chicken stalls, Dau district.  The sampling in this study were the customers of Ayam Nyungsep Dau Malang who had met the criteria as respondents, which were determined by the researcher, namely, having eaten or bought at least 3 times. From the results of this study, the following results were obtained: (1) Brand Image style, product innovation, and product quality simultaneously influence purchasing decisions. (2) Brand Image has partial effect on Purchase Decision. (3) product innovation has a partial effect on purchasing decisions. (4) Product quality has a partial effect on purchasing decisions..Keywords: Brand Image, Product Innovation,Product Quality, Buying Decision